Substitution Reaction of Hydroxy of Citronellol with Chloride Using A Mixture of Ammonium Chloride and Sulphuric Acid - Endah Sayekti; Imelda H Silalahi; Titin Anita Zaharah (UNIVERSITAS SEBELAS MARET (UNS), 2016)
Substitution reaction of hydroxy of citronellol with chloride using a mixture of ammonium chloride (NH4Cl) and sulphuric acid (H2SO4) has been conducted. The citronellol was obtained from the reduction of citronellal using sodium borohydride (NaBH4) at room temperature for 30 minutes. Substitution of hydroxy of citronellol with chloride ion was carried out at 80 oC and molarity ratio of citronellol and NH4Cl 1:1, 1:2; 1:3; and 1:4 respectively. Identification of the product by gas chromatography-mass spectrometry (GC-MS) showed that the substitution reaction produced 2-isopropyl-5-methyl-1-chlorocyclohexane compound with rendemen 64,49 % in mol ratio of 1:4. The infra red (IR) analysis showed that there was a vibration at wave number 763 cm-1 which is a typical C-Cl vibrations.